The Effect of Specific Exercises on the Speed of Motor Response and Accuracy of Receiving Service for Secondary School Students of Volleyball - Mona Jassim Rahim; Aseel Jaleel Gatia (Institute of Medico-legal Publications Pvt Ltd, 2021)
As for the research goals, they focused on developing specific exercises to develop the speed of the kinematicresponse and the accuracy of receiving service of volleyball, and to know the effect of these exercises indeveloping the speed of motor response and the accuracy of the receiving service for students of volleyball,this research was conducted on a sample of (12) medium-fat students, who were divided into two equalgroups, one experimental and the other control, each group consisting of (6) students, after conductingthe processes of homogeneity and parity, The appropriate tests for this skill were also chosen, with anexploratory experiment conducted on a group of medium-fat volleyball students from outside the basicresearch sample with the use of tools and aids in the research, pre-tests were conducted on the two groups,and then the vocabulary of specific exercises was applied within the educational units of (16) educationalunits. The time of each unit is (90) minutes by two units per week, the share of exercises within the mainsection of the educational unit was (30) minutes, the end of the educational units for this skill, the posttests were taken, and then treating the results of the research using appropriate statistical means. The tworesearchers came up with several conclusions, the most important of which was that the vocabulary of thespecific exercises that were used had a positive effect on developing the speed of motor response and theaccuracy of receiving service e volleyball.